In situ chemical and Sr–Nd–O isotopic compositions of apatite from the Tongshi intrusive complex in the southern part of the North China Craton: Implications for petrogenesis and metallogeny. (1st June 2015) - Xu, Wen-Gang; Fan, Hong-Rui; Hu, Fang-Fang; Santosh, M.; Yang, Kui-Feng; Lan, Ting-Guang
Highlights: Crustal contamination is demonstrated to take place in petrogenesis of syenite. Some apatites are survived during remelting of the protolith of monzonite. Gold mineralizing potential of syenite is greater than that of monzonite. Abstract: The Tongshi intrusive complex from the southeastern margin of the North China Craton is composed of syenite and monzonite, and was emplaced at ca. 180 Ma. Apatite from the syenite and monzonite were analyzed to better understand the petrogenesis of the complex and its mineralization potential. The cathodoluminescence images of some apatites from the monzonite exhibit core–rim texture, whereas the apatites from the syenite display uniform inner texture. The core and rim domains of the apatites exhibit distinct Sr isotopes and major–trace element compositions, whereas only little variation is displayed by the oxygen isotopes. The core portions of the apatites were inferred to be inherited from the protolith of the monzonite during remelting process. The calculated δ 18 O values of the syenite range from 3.5‰ to 4.1‰ with an average of 3.8‰ (SE = 0.21), which is significantly lower than that of the monzonite sample (with a range of 6.4–6.9‰, and mean at 6.7‰). In conjunction with the heterogeneity of Nd isotopic compositions (with normalized 143 Nd/ 144 Nd ratios varying from 0.51151 to 0.51236, and ε Nd ( t  = 180 Ma) values from −20.3 to −4.8) of the apatites from the syenite, it is proposed that the syenite melts may have been contaminated by crustal components which were earlier hydrothermally altered at high temperature. Based on element diffusion theory, we calculate the temperature of this crustal contamination to be higher than 637 °C, the closure temperature of Sm–Nd isotopic diffusion in apatite, and estimate that the duration of this process is probably shorter than 0.13 Ma. The oxygen fugacity of the syenite and monzonite calculated by apatite Mn content indicate that high oxidization state of the syenite magma can enhance the metallic mineralization potential. In contrast, the lower oxygen fugacity of the monzonite melt was unfavorable for metal enrichment, thus leading to insignificant mineralization. Our study recommends more focus for gold exploration in the rocks with syenitic affinities in this region.